The development and preliminary validation of a social-emotional skills assessment instrument for lower secondary school students - Einpaul Piret; Leijen Äli; Baucal Aleksandar (Psihološka Istraživanja)
Given the necessity of existence of comprehensive and psychometrically sound instruments that measure students' social-emotional skills (SEMS) in school context and facet-level, this study aims to develop and evaluate a SEMS assessment instrument for lower secondary school students. The initial version of the instrument was developed based on the descriptions of skills from the SEMS frameworks by Primi et al. and OECD and consisted of 48 items. After confirmatory factor analysis (CFA) with a sample of 204 students from Estonia, a 9-factor and 34-item instrument has been refined. This model has been confirmed with acceptable fitness by CFA with another sample of 521 students. Strict measurement invariance has been established between grade groups (grades 6 and 9). In conclusion, while analyses show promise and the instrument allows assessing students' SEMS in lower-secondary schools, further research is required.